Pengaruh Komite Audit, Ukuran Perusahaan Dan Profutabilitas Terhadap Tax Avoidance Pada Perusahaab Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia - Irmayani, Ade; Azhar, Iqlima; Muetia, Tuti (LPPM Universitas Labuhanbatu, 2022)
This study aims to dertemine the effect of the audit committee, on frime size and profitability on tax avoidance in textile and and garment companies listed on the Indonesia Stock Exchange (IDX) in 2011-2013. This type of research is a Quantitative population and the sample of this research is all companies listed on the Indonesia Stock Exchange (IDX). The sample is dertemined based on purposive sampling as many as 6 data from textile and garment companies. Data collection methods using literature studies and documentation of the results of the audit committee has no significant positive effect on frim size tax avoidanceÂ significant positive effect on tax avoidance, while profitabilitisynhas a significant negative effect on frim size and profitabilitiy have value Fsign 0,000<0,05 simultaneously effect tax avoidance.